Tropical Hurricane Charley (2004): Unpredicted Rapid Intensification - Shekriladze, Irakli G. (Journals of Georgian Geophysical Society, 2017)
In the past decade, one of the most resonant failure of prediction service has been associated with unpredicted rapid intensification of tropical hurricane (TH) Charley attacked on high power the southern-western Florida on August, 13, 2004. In the paper the results of analysis Charley’s development in the framework of so-called equilibrium translation model (ETM) are presented. ETM considers TH as an open dissipative system internally geared to maximum intensification. When this tendency is found to be aligned with large-scale environmental wind, TH gains highest efficiency in terms of conversion of the oceanic heat into the cyclonic motion of atmosphere (alignment effect), building a basis for the rapid intensification. ETM discloses crucial role of non-dimensional alignment number incorporating integral thermal and dynamical parameters of the system ocean-cyclone-atmosphere (OCA). The value of this parameter during rapid intensification (critical alignment number) turns out to be roughly constant for any TH. The analysis is made in the two approximations. The first approximation assumes circular geometry of TH without taking in account variability of its outer radius. The second approximation assumes non-circular geometry of TH with variable in time outer boundary